Rancang Bangun dan Analisis Rangka Traktor Pemanen Jagung - Rahman, Fhadel Aditya; Waskito, Waskito (Darul Yasin Al Sys, 2023)
A corn harvesting tractor is a tractor that operates using a diesel-powered engine which is used to harvest corn and is operated by humans. It is estimated that the presence of this tractor will lighten the burden on corn farmers who previously harvested using human power. Apart from making harvesting easier, corn harvesting tractors also increase production yields. This research aims to reveal the stress values that occur in the frame and the safety values from the results of the design of the tractor frame structure in the form of design and structural strength analysis. This research was limited to a loading of 200 kg. This research examines the design, simulation, and stress analysis of the frame structure of a 200 kg corn harvester tractor using the finite element method or can be said to be Finite Element analysis (FEA). ASTM A36 Steel material is used. Finite element analysis is carried out with a numerical system using software Solidworks 2020. The results of the simulation and analysis show that the tractor frame structure has a stress, deformation, and safety factor of 1.228e+07 N/m2, 2.934e-04 m, and 20.